Airway remodelling in COPD: It's not asthma!. Issue 8 (5th July 2016) - Jones, Robyn L.; Noble, Peter B.; Elliot, John G.; James, Alan L.
ABSTRACT: COPD is defined as airflow limitation that is not reversed by treatment. In asthma, airflow limitation is not only reversible, but also inducible. This is called 'airway hyperresponsiveness' (AHR) and is associated with thickening of the airway wall, predominantly the layer of airway smooth muscle, due to more cells, bigger cells and more extracellular matrix (ECM) in proportion to the increase in smooth muscle. AHR is also observed in COPD if the changes in airflow are expressed as a percent of the baseline lung function. However, the absolute change in baseline lung function that can be induced in COPD is actually less than that seen in normal subjects, suggesting that the airways in COPD are resistant not only to opening, but also to closing. This observation agrees with physiological measures showing increased airway wall stiffness in COPD. Like asthma, airway wall thickness is increased in COPD, including the layer of smooth muscle. Unlike asthma, however, fixed airflow obstruction appears to be characterized by a disproportionate increase in the ECM within the smooth muscle layer. In this review, we summarize the studies of airway matrix deposition in COPD and put forward the proposal that the airway remodelling in COPD is different from that in asthma and call for a systematic analysis of airway matrix deposition in COPD.